Tolerance allocation of complex assembly with nominal dimension selection using Artificial Bee Colony algorithm. (January 2019) - Vignesh Kumar, D; Ravindran, D; Lenin, N; Siva Kumar, M
Optimum tolerance allocation plays a vital role in minimizing the direct manufacturing cost of mechanical assembly. It is very sensitive due to the variations in manufacturing processes of the components. Most of the earlier studies are aiming at optimum tolerance allocation for assemblies without considering the selection of nominal dimensions of components and considering them as discrete values. It is proposed to minimize the manufacturing cost of an assembly with tolerance allocation and alternate nominal dimension selections by considering them in closer decimal intervals. The evolutionary algorithms such as Genetic and Artificial Bee Colony algorithms are developed and proposed to achieve the above objectives. The performance of the algorithms has been enhanced with the seed solution obtained using Lagrange Multiplier method. The complex assembly problems proposed by various authors with the required parameters have been considered for investigating the proposed method. The critical dimensions of the assemblies are fixed and the nominal dimension has been varied with its tolerances. The resultant manufacturing cost by various methods is presented and compared with corresponding nominal dimensions and tolerances. Based on the percentage of improvement of manufacturing cost, it is observed that the Artificial Bee Colony algorithm outperforms.